Prototype PLTPH Dengan Turbin Archimedes Screw Bilah Lima Berbasis IoT - Pratomo, Diah Ambarwati; Fahreza, Raya; Saputra, Zanu; Surojo, Surojo (Jurnal Inovasi Teknologi Terapan, 2024)
The use of Archimedes screw turbines in small-scale hydroelectric power plants is being developed as an option for renewable and environmentally friendly electricity sources with significant potential, particularly in remote areas. Another advantage is the ease of installation and maintenance of these turbines. The aim of this research is to generate environmentally friendly and sustainable electrical energy using water resources, leveraging the potential energy of water in our surroundings, and monitoring the small-scale hydroelectric power plant (PLTPH) system through a smartphone. Field testing results demonstrate a DC output voltage of approximately 21.50 volts at a 55˚ angle with a rotational speed of 600 rpm. Practical testing reveals an accuracy level of over 90% for the IoT monitoring values for rpm and water flow.